Pengaruh Manajemen Laba pada Nilai Perusahaan Sesudah Pergantian Chief Executive Officer (CEO) - Astiti, Ni Putu Sukma; Damayanthi, I Gusti Ayu Eka (E-Jurnal Akuntansi; Vol 23 No 1 (2018)DO - 10.24843/EJA.2018.v23.i01.p08, 2018)
Companies must optimize the value of the firm to attract the interest of creditors and investors, but in fact optimization of firm value is always disrupted by the agency conflict. The manager has more complete information about the company , it provides an opportunity for managers to do earnings management . One of the earnings management motivations is Chief Executive Officer (CEO) turnover . The purpose of this study is to determine the effect of earnings management on the value of the firm after CEO turnover at the manufacturing company listed on Indonesia Stock Exchange (BEI) in 2008-2016. The number of samples in this study are 32 companies obtained by purposive sampling method. Data collection method of this research is non participant observation. Data analysis technique used is simple linear regression. The result of analysis shows that earnings management with income decreasing scheme during first year after CEO turn over has negative and significant effect on firm value, and earnings management with income increasing scheme during second year after CEO turn over has positive and significant effect on firm value . Keyword : firm value, earnings management, CEO turnover.